A Review of Recent Studies of Dynamometers for Cutting Force Measurement in Machining Processes - Raheem, A. (Institute of Electrical and Electronics Engineers Inc., 2021)
Accurate measurement and high-performance innovations provide an ideal basis for Industry 4.0. The manufacturing sectors involving a wide range of quality and precision standards are operating in an exceptionally challenging environment. To optimize the process efficiency of the manufacturing sector, the integration of reliable cutting force measurement strategies is indispensable. In this regard, a dynamometer is an inclusive tool, which is pertinent to lay the foundation of zero-defect industrial production. Recently, cutting force measurement strategy has been repeatedly used in diverse studies to help better understand the mechanics of machining, tool design, tool condition, process optimization, etc. These studies were focused on the varied elastic element, materials, sensors, sensitivity, rigidity, cross-interference, etc. However, no study reviews the existing literature on recent trends and future research prospects. Therefore, there is a need for an up-to-date systematic review of such studies. To achieve this, recent publications on cutting force dynamometers from 2011 to 2020 were reviewed and analyzed. The analysis showed that recent studies were focused on process integrated monitoring while covering multiple aspects regarding design and development. However, a good number of reviewed studies overlooked the cost analysis, analysis of static and dynamic properties of the designed dynamometer. Based on the challenges in the design, utilization, and development of dynamometer, future research prospects were also presented. Â© 2021 IEEE.